2019
DOI: 10.2196/13041
|View full text |Cite
|
Sign up to set email alerts
|

Avatar-Based Patient Monitoring With Peripheral Vision: A Multicenter Comparative Eye-Tracking Study

Abstract: Background Continuous patient monitoring has been described by the World Health Organization as extremely important and is widely used in anesthesia, intensive care medicine, and emergency medicine. However, current state-of-the-art number- and waveform-based monitoring does not ideally support human users in acquiring quick, confident interpretations with low cognitive effort, and there are additional problematic aspects such as alarm fatigue. We developed a visualization technology (Visual Patie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(48 citation statements)
references
References 38 publications
2
44
0
Order By: Relevance
“…Additionally, the technology improved perceptive performance in a setting with a distraction [25]. In eye-tracking studies, we found that the technology works because users do not need to read numbers sequentially but can receive information from looking at colorful moving objects, which allows for monitoring using peripheral vision and enables parallel perception of multiple vital signs at the same time [26,27].…”
Section: Visual Patient Technologymentioning
confidence: 93%
“…Additionally, the technology improved perceptive performance in a setting with a distraction [25]. In eye-tracking studies, we found that the technology works because users do not need to read numbers sequentially but can receive information from looking at colorful moving objects, which allows for monitoring using peripheral vision and enables parallel perception of multiple vital signs at the same time [26,27].…”
Section: Visual Patient Technologymentioning
confidence: 93%
“…This eye-tracking study by Pfarr et al published in 2019 [4] follows the same theoretical background as the Visual Patient series 1 eye-tracking study [3]. According to these neurophysiological principles, a person can only read glyphs when they look at them with foveal or sharp vision.…”
Section: Peripheral Visionmentioning
confidence: 98%
“…We generated empirical evidence for peripheral vision monitoring through eye-tracking studies [4]. Because of the way the avatar displays the information as colorful moving graphical objects, caregivers can monitor some of the patient's vital signs using only their peripheral field of view.…”
Section: Peripheral Vision Monitoringmentioning
confidence: 99%
See 2 more Smart Citations